A single center phase II study of ixazomib in patients with relapsed or refractory cutaneous or peripheral T‐cell lymphomas. Issue 12 (25th September 2017) - Boonstra, Philip S.; Polk, Avery; Brown, Noah; Hristov, Alexandra C.; Bailey, Nathanael G.; Kaminski, Mark S.; Phillips, Tycel; Devata, Sumana; Mayer, Tera; Wilcox, Ryan A.
Abstract: The transcription factor GATA‐3, highly expressed in many cutaneous T‐cell lymphoma (CTCL) and peripheral T‐cell lymphomas (PTCL), confers resistance to chemotherapy in a cell‐autonomous manner. As GATA‐3 is transcriptionally regulated by NF‐κB, we sought to determine the extent to which proteasomal inhibition impairs NF‐κB activation and GATA‐3 expression and cell viability in malignant T cells. Proteasome inhibition, NF‐κB activity, GATA‐3 expression, and cell viability were examined in patient‐derived cell lines and primary T‐cell lymphoma specimens ex vivo treated with the oral proteasome inhibitor ixazomib. Significant reductions in cell viability, NF‐κB activation, and GATA‐3 expression were observed preclinically in ixazomib‐treated cells. Therefore, an investigator‐initiated, single‐center, phase II study with this agent in patients with relapsed/refractory CTCL/PTCL was conducted. Concordant with our preclinical observations, a significant reduction in NF‐κB activation and GATA‐3 expression was observed in an exceptional responder following one month of treatment with ixazomib. While ixazomib had limited activity in this small and heterogeneous cohort of patients, inhibition of the NF‐κB/GATA‐3 axis in a single exceptional responder suggests that ixazomib may have utility in appropriately selected patients or in combination with other agents.